ESTERIFIKASI MINYAK GORENG BEKAS DENGAN KATALIS H2SO4 DAN TRANSESTERIFIKASI DENGAN KATALIS CaO DARI CANGKANG KERANG DARAH: VARIASI KONDISI ESTERIFIKASI - Apriani Sartika; Nurhayati '; Muhdarina ' (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2015)
Fuel that becomes important requirement of Indonesian is more dwindling and will run out within the next 12 years. Therefore, the development of alternative fuels that are environmentally friendly is needed. One example of an environmentally friendly alternative fuel is biodiesel. This study aimed to synthesize biodiesel from used cooking oil by esterification and transesterification step and determine the optimum conditions. The parameters varied are the reaction esterification which weight of H2SO4 catalyst and mole ratio of oil:methanol, while temperature and reaction time was remained variable. Transesterification reaction parameters was remained variable. The analysis showed that the conversion of biodiesel was 70,35% obtained by the optimum condition of esterification was weight of H2SO4 catalyst was 3%, the mole ratio of oil: methanol was1:18, temperature was 70oC, and reaction time was 3 hours. Based on this results, it can be concluded that the used cooking oil can be used as raw material for biodiesel synthesis.